PERSEPSI KELUARGA TERHADAP PENYAKIT KRETIN DI KABUPATEN MAGELANG, PURWOREJO DAN WONOSOBO - , Muh.Faozan, Toto Sudargo, SKM, M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background : Iodine Deficiency Disorders (IDD) is one of the main nutrition problems in Indonesia. Cretin is a further caused from fetal iodine deficiency. Qualitative Research in Magelang District showed that goiter was not considered as a disease and not an obstacle to perform their daily activities. Objective : To determine the family perceptions of cretin in Magelang District, Purworejo and Wonosobo. Methods : This study used qualitative methods with ethnographic design focused. Methods of data collection were in-depth interviews, observation and documentation. In-depth interviews conducted in 15 people of cretins family aged 23 to 62 years. Observations carried out by participatory observation for 7 days in 3 cretinâs families. Documentation was done by collecting all relevant documents related with cretins and their families. Results : Family perception about the causes, characteristics, treatment, and prevention of cretinâs disease due to the less of height, disrupted activities and intelligence retardation. The families believed that cretin is a disease, but they did not understand properly the causes, characteristics, consequences, prevention and treatment of cretins. Families sincerely receive the family members who suffer cretins. There were differences in perceptions and family behavior towards cretins. Family of cretins in Wonosobo District considered that cretins were only a matter of lack of height, while families in the District of Magelang and Purworejo considered that in addition to the lack of height it also disturbed the physical activities and intelligence retardation. Conclusion :. It is necessary to perform attention and seriousness from all parties in order to increase knowledge and understanding of the family about the cretin disease and Iodine Deficiency Disorder (IDD).